Pengaruh Corporate Social Responsibility, Kualitas Audit, Ukuran Perusahaan Terhadap Earning Response Dengan Struktur Modal Sebagai Variabel Coefficient Moderasi - El Kavi, Naura Adena; Nuryatno Amin, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research seeks to investigate the correlation between corporate social responsibility, audit quality, and company size in relation to the earning response coefficient, with capital structure as the moderating factor among firms listed on the Indonesia Stock Exchange throughout the 2019-2022 period. The study focuses on companies within the consumer non-cyclical sector listed on the Indonesia Stock Exchange during 2019-2022. Employing purposive sampling, 116 samples were selected within this timeframe. Quantitative data analysis using SPSS version 26.0 was employed to conduct multiple linear regression analysis for data processing. The findings of this investigation demonstrate a positive correlation between corporate social responsibility, audit quality, and firm size with the earning response coefficient. Moreover, it was observed that while capital structure acts as a moderator that reinforces the positive impact of corporate social responsibility and audit q